Study of Alternative Radiation Material Shielding for Gamma Radiation using Monte Carlo Simulation - Urfa, Gusti Atika; Wianto, Totok; Manik, Tetti Novalina; Nasrulloh, Amar Vijai (Pusat Teknologi Dan Keselamatan Reaktor Nuklir (PTKRN), 2023)
Lead as the most commonly used material for radiation shielding but possessing toxic properties. This research aims to identify alternative, lead-free, and non-toxic materials for gamma radiation shielding through Monte Carlo simulations. Bismuth Oxide (Bi2O3), Barium Oxide (BaO), Tungsten Trioxide (WO3), Tungsten Dioxide (WO2), and Molybdenum Trioxide (MoO3) were selected as potential substitutes for lead. Pure lead (Pb) and Lead Oxide (PbO) were used for comparison. The simulation were performed using Particle Heavy Ion Tracking System (PHITS) software, with a gamma energy of 662 keV. The result of the simulation shows that the linear attenuation coefficient values for Pb and PbO were 0.902 mm-1 and 0.74 mm-1, respectively. Meanwhile, the simulation results of those simulated materials that are closest to Pb and PbO are Bi2O3 and WO2 with an attenuation coefficient of 0.71 mm-1. This simulation shows that for non-lead materials, BiO2 and WO2 have potential as alternative of non-lead radiation shielding.